THE CONCEPT OF ISLAMIC EDUCATION ACCORDING TO THE EDUCATION OF IBNU MISKAWAIH AND AL-GHAZALI - Alimin, Husain Abdullah (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the concept of Islamic education according to the education of Ibnu Miskawaih and Al-Ghazali with various studies as a stream based on the science of Islamic religious education. This study uses a descriptive qualitative approach. The analytical method used in this study is the data that is analyzed descriptively and qualitatively by using various theoretical foundations related to the object of research and it is used as a basic reference for qualitative analysis. The results of the analysis examine for Ibnu Miskawaih in detail about the concept of Islamic education according to the education of Ibnu Miskawaih and Al-Ghazali with efforts to form a Muslim personality as the ultimate goal of education that requires a continuous process throughout life so that it does not stop at the limit of human adult achievement. Abstrak: Kajian ini bertujuan untuk mengetahui konsep pendidikan Islam menurut pendidikan Ibnu Miskawaih dan Al-Ghazali dengan berbagai kajian sebagai aliran yang didasarkan pada ilmu pendidikan agama Islam. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Metode analisis yang digunakan dalam penelitian ini adalah data yang dianalisis secara deskriptif kualitatif dengan menggunakan berbagai landasan teori yang berkaitan dengan objek penelitian dan dijadikan sebagai acuan dasar analisis kualitatif. Hasil analisis mengkaji secara rinci tentang konsep pendidikan Islam menurut pendidikan Ibnu Miskawaih dan Al-Ghazali dengan upaya membentuk kepribadian muslim sebagai tujuan akhir pendidikan memerlukan proses yang berkesinambungan sepanjang hayat sehingga tercapai tidak berhenti pada batas pencapaian manusia dewasa.